Effects of Calcium, Phosphorus and Manganese Supplementation During Oil Palm Frond Fermentation by Phanerochaete chrysosporium on Laccase Activity and in vitro Digestibility - Jamarun, Novirman; Zain, Mardiati; Arief; Pazla, Roni (Pakistan Journal of Nutrition, 2017)
Objective: The objective of this study was to evaluate the effects of calcium (Ca), phosphorus (P) and manganese (Mn) supplementation during Oil Palm Frond (OPF) fermentation by Phanerochaete chrysosporium on laccase activity and in vitro fiber digestibility. Materials and Methods: This study was carried out using a randomized block design with 3 treatments (Addition of Ca, P and Mn) and 5 replications. The following treatments were performed: T1 = Ca 2000+P 1000+Mn 150 ppm, T2 = Ca 2000+P 1500+Mn 150 ppm, T3 = Ca 2000+P 2000+Mn 150 ppm. The data were subjected to an analysis of variance (ANOVA) and differences between treatment means were tested using Duncan’s Multiple Range Test (DMRT). The parameters measured were as follows: Laccase activity (U mL –1), Neutral Detergent Fiber (NDF) digestibility (%), Acid Detergent Fiber (ADF) digestibility (%), cellulose digestibility (%) and hemicellulose digestibility (%). Results: Results revealed that laccase enzyme activity, NDF digestibility, ADF digestibility and cellulose digestibility were significantly increased by the addition of P in T3. However, T2 and T3 non-significantly affected (p>0.05) the digestibility of hemicelluloses. Conclusion: It is concluded that supplementation of OPFs with Ca 2000, P 2000 and Mn 150 ppm resulted in the highest laccase activity and in vitro fiber digestibility.